2019
DOI: 10.1007/s40415-019-00515-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus and growth phases on the transcription levels of EPA biosynthesis genes in the diatom Phaeodactylum tricornutum

Abstract: Polyunsaturated fatty acids (PUFAs) are essential in the animal diet, notably eicosapentaenoic and docosahexaenoic acids (EPA and DHA, respectively), and in recent years, microalgae like marine diatoms are being considered as an alternative source of PUFA. Therefore, this study evaluated the effect of three nitrogen/phosphorus (N/P) ratios (21/1, 14/1 and 7/1) and two growth phases (exponential and stationary) on both EPA concentration and gene transcript levels, four front-end desaturases and two elongases, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Silicon tends to polymerise, so the concentration of the assimilable silicon decreases. If the rate of consumption of the assimilable monomeric and dimeric form of silicon by diatom is higher than their generation by depolymerisation from silicon polymers [ 35 , 36 ], it could limit diatom growth, resulting in a decrease in specific growth rates, the concentration of biomass, and cell number at higher Si concentrations (1.5 and 2 mM). Some authors also observed an inhibitory effect in the presence of high silicon concentration [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Silicon tends to polymerise, so the concentration of the assimilable silicon decreases. If the rate of consumption of the assimilable monomeric and dimeric form of silicon by diatom is higher than their generation by depolymerisation from silicon polymers [ 35 , 36 ], it could limit diatom growth, resulting in a decrease in specific growth rates, the concentration of biomass, and cell number at higher Si concentrations (1.5 and 2 mM). Some authors also observed an inhibitory effect in the presence of high silicon concentration [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, cells exposed to DA in the LAG phase of growth also exhibited a higher decrease in AH − content, as compared to cells in the EXP growth phase. The different behavior observed among the growth phases could be influenced by the diverse nutrient availability and metabolism in each phase, being more active in the EXP phase [ 51 , 52 ]. To assess the magnitude of the ability of the antioxidant defense network to control the oxidant effects of DA exposure in the cells in the three phases of development, damage markers should be evaluated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Yongmanitchai and Ward [33] cultured P. tricornutum in Mann Myers medium and increased the P concentration from 2.5-fold to 5-fold higher than the control, and they found no significant differences in total biomass content among all the treatments. Recently, Lopes et al [34] cultured P. tricornutum in F/2 medium and increased the P concentration from 1.5-fold to 3-fold higher than the control, finding the same results as Yongmanitchai and Ward [33]. On the other hand, in studies carried out in Chaetoceros muelleri grown in F medium, P concentration was doubled compared to the control, and a higher content of dry biomass was found in the control treatment compared to the P excess treatment.…”
Section: P Effect On Growth and Biomass Productionmentioning
confidence: 99%
“…Another characteristic fatty acid is eicosapentaenoic acid (EPA), which can represent more than 10% of the total fatty acid profile of diatoms [132,138,139]. It has been widely reported in microalgae that culture phases and different abiotic factors, such as temperature, light, CO 2 supply and nutrient availability (such as P), influence the fatty acid content, and diatoms are not an exception [34,[140][141][142].…”
Section: Influence Of P Availability On Lipid Accumulation In Diatomsmentioning
confidence: 99%
See 1 more Smart Citation